Peran Psikologi Manajemen dalam Meningkatkan Motivasi Guru dan Efektivitas Sekolah - Widya Isma Dayanti; Husnul Hotimah; Rudi Khobiron; Mu’alimin Mu’alimin (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2026)
Due to its focus on the psychological components of leadership, motivation, communication, and human resource development in educational institutions, management psychology is becoming an increasingly significant perspective in educational management. The use of management psychology in the classroom is considered crucial for improving organizational performance and teacher motivation. The purpose of this study was to investigate how management psychology can enhance teacher work motivation and its impact on school efficacy. This study reviewed previous research on the use of management psychology in education using a qualitative approach and literature review methodology. Using keywords related to management psychology in education, teacher motivation, educational leadership, and educational organizational performance, systematic search of scientific publications published in the Google Scholar database between 2022 and 2026 was used to collect data. Identification, screening, eligibility evaluation, and final selection of relevant publications were all steps in the literature selection process. Thematic coding techniques were used to examine six selected publications to determine the main findings, methodology, and research emphasis of each study. The findings suggest that the use of management psychology in educational management techniques, such as effective communication, teacher empowerment, supportive leadership, and the establishment of equitable reward systems, can significantly enhance teacher motivation and foster a positive work environment. In addition, these approaches increase the effectiveness of educational institutions, improve teacher performance, and foster collaboration within the school environment. To promote teacher professional development and raise the overall standards of educational institutions, it is crucial for educational administrations to incorporate a psychological perspective.